2015
DOI: 10.1007/s12237-015-0047-z
|View full text |Cite
|
Sign up to set email alerts
|

A Field Study of How Wind Waves and Currents May Contribute to the Deterioration of Saltmarsh Fringe

Abstract: Deltaic landscapes, such as the Mississippi River Delta, are sites of extensive conversion of wetlands to open water, where increased fetch may contribute to erosion of marsh edges, increasing wetland loss. A field experiment conducted during a storm passage tested this process through the observations of wave orbital and current velocities in the fringe zone of a deteriorating saltmarsh in Terrebonne Bay, Louisiana. Incident waves seaward of the marsh edge and wave orbital and current velocities immediate lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…Correspondingly, the bottom stresses due to wave forcing are greater (up to 0.4 Pa) on the shallower flanks than in the channel (less than 0.1 Pa; Figure ). These regions of enhanced frictional dissipation correspond with wave‐induced bottom stresses that are more intensified locally than previously found in shallower and more spatially uniform estuaries (Karimpour et al, , ; Mariotti & Fagherazzi, ; Mariotti et al, ). For the northwest wind conditions, the simulated wave‐induced bottom stresses increase from around 0.1 Pa in the upwind region of the middle estuary to more than 0.3 Pa in the downwind region of the lower bay.…”
Section: Results Of Realistic Domain Simulationssupporting
confidence: 50%
See 1 more Smart Citation
“…Correspondingly, the bottom stresses due to wave forcing are greater (up to 0.4 Pa) on the shallower flanks than in the channel (less than 0.1 Pa; Figure ). These regions of enhanced frictional dissipation correspond with wave‐induced bottom stresses that are more intensified locally than previously found in shallower and more spatially uniform estuaries (Karimpour et al, , ; Mariotti & Fagherazzi, ; Mariotti et al, ). For the northwest wind conditions, the simulated wave‐induced bottom stresses increase from around 0.1 Pa in the upwind region of the middle estuary to more than 0.3 Pa in the downwind region of the lower bay.…”
Section: Results Of Realistic Domain Simulationssupporting
confidence: 50%
“…Wave energy dissipation is strongly tied to spatial gradients in bathymetry, particularly in the lower bay, as waves that are at equilibrium in deeper water propagated into shallower regions and are subject to greater bottom friction. These regions of enhanced frictional dissipation correspond with wave‐induced bottom stresses that are more intensified locally than previously found in shallower and more spatially uniform estuaries (Karimpour et al, , ; Mariotti et al, ; Mariotti & Fagherazzi, ). Although the energy dissipation due to bottom friction is small overall compared with dissipation by whitecapping, over steeply sloping topography bottom friction dissipation greatly exceeds the equilibrium balance.…”
Section: Discussionsupporting
confidence: 50%
“…A critical feature of such restoration projects is to understand how erosion may contribute to wetland loss in these shallow environments, where depth and fetch are perceived to limit wave generation. There is increased awareness that even in shallow estuaries dominated by wetland vegetation, the wave activity contributes to processes such as sediment re-suspension, mudflat erosion, turbidity alteration, marsh edge erosion and wetland losses78910.…”
mentioning
confidence: 99%
“…Previous studies suggested that wind wave activities in wetland dominated estuaries are a potential factor in enhancing and accelerating wetland loss rates1011, which fundamentally can affect the physics and biology of estuaries. The conversion of wetlands to water caused by wind waves in shallow estuaries, leads to further increases in wind fetch, which consequently causes wave generation with higher energy.…”
mentioning
confidence: 99%
See 1 more Smart Citation